Interference-aware node access scheme in UAV-aided VANET - Xiying FAN; Chuanhe HUANG; Junyu ZHU; Shaojie WEN (Tongxin xuebao)
In vehicular Ad Hoc network (VANET),frequent link handovers and channel interference can lead to increased transmission delay and decreased network throughput.To address the issues,unmanned aerial vehicle (UAV) were introduced to cooperate with vehicles and construct UAV-assisted air-ground integrated VANET.An interference-aware node access scheme was proposed.The node access problem was formulated as a multi-objective optimization problem considering link transmission rate,link handovers and transmit power.Then the optimization problem was decomposed into two convex optimization sub-problems by dual decomposition method,the sub-problem jointly optimizes handovers and link transmission rate while the sub-problem optimizes the transmit power based on link reliability.Finally,simulation results show that the proposed mechanism can effectively improve data delivery ratio,average end-to-end delay and network throughput.